ANALISIS KINERJA NON FINANCIAL TERHADAP KEPUASAN KERJA DAN PRESTASI KERJA - Chara Pratami Tidespania Tubarad (Faculty of Economics and Business, 2019)
Nowadays the performance of Civil Servants (PNS) related to service to the community has always been the spotlight. The low work discipline, awareness, and service shown by some of the Civil Servants has an impact on negative stereotypes provided by the community. Therefore there is a need for significant improvements so the performance of government employees can be as expected. Because undisciplined work behavior can result in a reduction in the performance of Civil Servants in general, especially in the Lampung Regional, coupled with negative opinions from the public because in the presentation of financial statements they cannot be accountable and timely. Non-financial performance affects work performance and job satisfaction affects work performance